Validated dynamic analysis of real sports equipment using finite element - a case study using tennis rackets - Allen, T.; Hart, J.; Spurr, J.; Haake, S.; Goodwill, S. (Procedia Engineering, 2010)
An explicit finite element (FE) model of a tennis ball impact on a freely suspended racket was produced in Ansys/LS-DYNA 10.0. The geometry for the racket frame was reproduced in the FE model using a non-contact laser scanner. The model was validated against experimental data obtained using the fully automated International Tennis Federation Racket Power Machine. The root mean squared error between the model and experimental data was 1m[dot operator]s-1 for the rebound velocity of the ball for typical velocities of over 40m[dot operator]s-1. The method can be applied to different rackets and other sports equipment to determine rapidly the performance characteristics of new designs.